2013
DOI: 10.1042/cs20130036
|View full text |Cite
|
Sign up to set email alerts
|

Non-alcoholic fatty liver disease is associated with an increased prevalence of atrial fibrillation in hospitalized patients with Type 2 diabetes

Abstract: NAFLD (non-alcoholic fatty liver disease) and AF (atrial fibrillation) are two pathological conditions that are highly prevalent in developed countries and share multiple risk factors. The relationship between NAFLD and AF in Type 2 diabetes is currently unknown. We studied a hospital-based sample of 702 patients with Type 2 diabetes discharged from our Division of Endocrinology during 2007-2011. The diagnosis of AF was confirmed in affected participants on the basis of ECGs and medical history by experienced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
108
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(117 citation statements)
references
References 38 publications
4
108
0
5
Order By: Relevance
“…Again, no patients were treated with pioglitazone or glucagon-like peptide-1 receptor agonists, which have been shown to reduce hepatic steatosis [1,9,25] and improve cardiac function [26,27]. Finally, our novel finding of a significant association between NAFLD and larger left atrial volume might also be of pathophysiological relevance in the explanation of recent observations documenting that type 2 diabetic patients with NAFLD are at risk of atrial fibrillation [28,29]. Collectively, our results suggest that NAFLD may contribute to impairments of both active and passive LV diastolic properties that are most probably additive to the myocardial defects already present in type 2 diabetes.…”
Section: Discussionsupporting
confidence: 51%
“…Again, no patients were treated with pioglitazone or glucagon-like peptide-1 receptor agonists, which have been shown to reduce hepatic steatosis [1,9,25] and improve cardiac function [26,27]. Finally, our novel finding of a significant association between NAFLD and larger left atrial volume might also be of pathophysiological relevance in the explanation of recent observations documenting that type 2 diabetic patients with NAFLD are at risk of atrial fibrillation [28,29]. Collectively, our results suggest that NAFLD may contribute to impairments of both active and passive LV diastolic properties that are most probably additive to the myocardial defects already present in type 2 diabetes.…”
Section: Discussionsupporting
confidence: 51%
“…Not surprisingly, the adjustment for fatty liver has attenuated the association between GGT and CVD mortality (58). Nonalcoholic fatty liver disease is associated with the risk of ventricular arrhythmias (85) and atrial fibrillation (86). In particular, elevated GGT is associated with the increased risk for atrial fibrillation either because both conditions share similar risk factors or because of ectopic fat accumulation in atrial myocardium (87) which may modulate the electrophysiological properties and ion currents predisposing for arrhythmogenesis (88).…”
Section: Mechanisms Of Ggt Association With Cvdmentioning
confidence: 99%
“…NAFLD is associated with elevated cardiovascular risk [8] [9][10] with increased fat mass as an important mediator. We showed that accumulation of inflammatory cells in visceral and not subcutaneous adipose tissue is associated with severity of NAFLD in morbid obesity [11] [12].…”
Section: Introductionmentioning
confidence: 99%